Analytical Studies on Gender Equality in Quran - Syarifan Nurjan; Muhamad Uyun (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
Gender equality in the Quran began to attract discussed by the Mufassirs to find a rational explanation of some verses that seem discriminatory against women, namely equality in creation, prophetic equality, equality in marriage (divorce, polygamy, interfaith marriage and leadership in the family), equality in inheritance, and equality in the public role. Rationality all the Quranic doctrine of the problems of gender equality lies in the notion of equality. If equality means that all something must be the same, then of course be interpreted in several verses that looks attitudes discriminatory against women. But if equality is defined in a professional manner, the differences in status, laws, rights, and obligations between men and women are not can be considered as discriminatory against women, since the differences partly due to the nature of each other and the technical functional. Analytical studies on professional equality such as interpretation of the verses of the Koran which is non-discriminatory, non-apological, biased - both male and patriarchal biases and female and matriarchic biases - and neither misogynistic towards women, a balanced interpretation between text and context is also needed, both the context when the verses were revealed, and the context of the verses were interpreted